Pandora's box : how guts, guile, and greed upended TV - Biskind, Peter (William Morrow, an imprint of HarperCollins Publishers, 2023)
"Bestselling author of Easy Riders, Raging Bulls and Down and Dirty Pictures, cultural critic Peter Biskind turns his eye toward the new golden age of television, sparked by the fall of play-it-safe network TV and the rise of boundary-busting cable followed by streaming, that overturned both--based on exclusive, candid, and colorful interviews with executives, writers, showrunners, directors, and actors"--